Difficulties Faced by Second Language Learners in Using Collocation - Sarah Nazar Kadhem; Fatima Shawqi Ismail (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This paper reviews the challenges encountered by second language learners in the  acquisition  and  utilization  of  collocations,  which  are  crucial aspects of proficient language use. Collocations refer to the habitual pairing or grouping of words  that  occur  together  frequently  in  natural  language.  The  research synthesizes findings from various studies conducted in the field, highlighting common difficulties experienced by learners across different proficiency levels and linguistic backgrounds. Key factors contributing to these challenges include differences  in  first  language  structures,  inadequate  exposure  to  authentic language use, limited awareness of collocational patterns, and difficulties in achieving  native-like  fluency.  Additionally,  pedagogical  implications  and effective  instructional  strategies  for  enhancing  collocational competence are discussed,  is to inform language instructors and curriculum developers in building more targeted and effective language learning materials and activities.This  research  is  divided  into  three  sections;  section  one  presents  the preliminaries   of   the   study.   Section   two   explains   the   meaning,   types, characteristics, and importance of the study. Section three will apply a test of collocation on the 4th stage of the college to know their weakness points in collocation. Finally, the conclusion is the research.